Cultural Influences on Managerial Choice: An Empirical Study of Employee Benefit Plans in the United States - Oliver, Elizabeth Goad; Cravens, Karen S. (Journal of International Business Studies, 1999)
The objective of this study is to determine the effect of culture on the provision of employee benefits. Cultural influences have been investigated from a variety of perspectives, but not in the context of pension and welfare benefits. Using unique data, this study analyzes the level of coverage of employee benefits in the United States. Results indicate that culture does have an effect on the provision of these benefits.